The Lottery: A Study of Narrative Irony and Its Role in Exploring Human Nature - Devita Luci Avista; Garnis Niken Ayu Salindri (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The purpose of this study was to identify and analyze various forms of narrative irony contained in Shirley Jackson's short story "The Lottery." This qualitative study used an in-depth text analysis approach to the narrative of the short story. This research method involved structural analysis to identify important narrative elements such as conflict, plot, and character. Using an irony analysis approach, this study examined how Shirley Jackson used this technique to highlight contradictions in human behavior and society. This study provided a deeper understanding of how narrative ironies function in literary works to stimulate critical thinking about human nature.